Immunity to change : how to overcome it and unlock potential in yourself and your organization - Kegan, Robert. (Leadership for the common good., 2009)
In Immunity to Change, authors Robert Kegan and Lisa Lahey show how our individual beliefs--along with the collective mind-sets in our organizations--combine to create a natural but powerful immunity to change. By revealing how this mechanism holds us back, Kegan and Lahey give us the keys to unlock our potential and finally move forward. And by pinpointing and uprooting our own immunities to change, we can bring our organizations forward with us. This persuasive and practical book, filled with hands-on diagnostics and compelling case studies, delivers the tools you need to overcome the forces of inertia and transform your life and your work.